2012
DOI: 10.1186/1477-7827-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional changes in thyroid function: a longitudinal study

Abstract: BackgroundLimitations in our current knowledge of normative physiologic changes in thyroid function during the periconception window narrow our ability to establish an optimal approach to screening and diagnosis of thyroid disease in pregnant women. The objective of this study was to characterize changes in thyroid function during the transition from the pre-pregnant to pregnant state in normal fertile women.MethodsWomen (N = 60) ages 30-42 years without a history of thyroid disease, who were planning pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, the complexity and dynamics of the hormonal changes occurring during pregnancy, especially in the first trimester, make the establishment of reference values more difficult. Changes in iodine metabolism, the production of chorionic gonadotropin (beta-hCG), increases in thyroid hormone carrier proteins, changes in excretion and elevation of thyroid hormones levels per se, alter the reference values (26). Thus, it is important that laboratories establish referen-surgery (30); untreated primary adrenal insufficiency (31); cross-reaction of TSH with heterophilic antibodies against rat proteins (32); and mutations in the TSH receptor (33).…”
Section: How Should Sch Be Diagnosed?mentioning
confidence: 99%
“…However, the complexity and dynamics of the hormonal changes occurring during pregnancy, especially in the first trimester, make the establishment of reference values more difficult. Changes in iodine metabolism, the production of chorionic gonadotropin (beta-hCG), increases in thyroid hormone carrier proteins, changes in excretion and elevation of thyroid hormones levels per se, alter the reference values (26). Thus, it is important that laboratories establish referen-surgery (30); untreated primary adrenal insufficiency (31); cross-reaction of TSH with heterophilic antibodies against rat proteins (32); and mutations in the TSH receptor (33).…”
Section: How Should Sch Be Diagnosed?mentioning
confidence: 99%
“…In a study of 60 women, Balthazar and Steiner looked at periconceptional changes in TSH levels. 39 They found that in women with antithyroid antibodies, TSH levels were more variable from the preconceptional to early pregnancy stage compared with women without antithyroid antibodies. 39 Other theories have included associated alterations in cytokines and T-helper cells.…”
Section: Antithyroid Antibodiesmentioning
confidence: 98%
“…39 They found that in women with antithyroid antibodies, TSH levels were more variable from the preconceptional to early pregnancy stage compared with women without antithyroid antibodies. 39 Other theories have included associated alterations in cytokines and T-helper cells. In a small study of 53 pregnant women, Turhan Iyidir et al found that women with thyroid autoimmunity had higher levels of IL-2 and IL-17 compared with controls.…”
Section: Antithyroid Antibodiesmentioning
confidence: 98%
“…Pre-pregnancy TSH values were significantly higher than those in early pregnancy, although no such changes in free T4 values were noted. 35 Thus, it appears that thyroid hormone levels differ in preconception versus early pregnancy, which should be taken into consideration when crafting screening guidelines.…”
Section: Physiologic Thyroid Function Changes In Pregnancymentioning
confidence: 99%